Acknowledgement to Reviewers of Pharmaceutics in 2017 - Pharmaceutics Editorial Office (MDPI AG, 2018)
Peer review is an essential part in the publication process, ensuring that Pharmaceutics maintains high quality standards for its published papers [...]